The Du Toitskloof Tunnel project : the construction of the (south) soft ground tunnel, Western Cape, South Africa - Goedhart, Michael H (Department of Construction Economics and Management, 2020)
The four kilometre twin-bore Du Toitskloof Tunnel is situated in the Klein Drakenstein mountain range, approximately 60 kilometres from Cape Town, near the town of Paarl. The tunnel will form part of the new National road system, upgraded to a freeway standard, linking Johannesburg and Cape Town. The subject of this report is the construction of the Du Toitskloof tunnel, with emphasis on the excavation and construction of the soft ground tunnel, by means of artificial ground freezing for ground support and stabilisation. The soft ground section of the tunnel being situated at the Western portal, and forming approximately 168 metres of the four kilometre main tunnel. The objectives of the report are: 1. to investigate the general history of tunnelling through the ages. 2. to investigate the general aspects and conditions surrounding the Du Toitskloof Tunnel project. 3. to investigate the pertinent geological investigations and conditions which prevail within the tunnel project. 4. to investigate the formation of the main tunnel within the Soft Ground tunnel contract. 5. to investigate the application of the system of artificialground freezing, inserting ground stabilisation, within the decomposed-weathered granite zone of the main soft ground tunnel project. 6. to investigate the methods of testing and monitoring the freezing process being applied to the soft ground for implementing temporary support. 7. to investigate the application of a reinforced Shotcrete lining against the frozen ground of the Du Toitskloof Soft Ground tunnel. 8. to investigate the possible alternatives for the excavation of the Soft Ground section of the Du Toitskloof tunnel.